2019
DOI: 10.14744/turkpediatriars.2019.66564
|View full text |Cite
|
Sign up to set email alerts
|

Alpha lipoic acid intoxication in an adolescent girl - Case report and review of the literature

Abstract: Alpha-lipoic acid is a widely used medication that does not need a prescription. Although it is safely used in adults, hitherto no safe dose for children has been reported, and there is no known antidote. The medical literature provides four reports of alpha-lipoic acid intoxication in the pediatric population to date. This case-report is the lowest known dose of alpha-lipoic acid intake leading to poisoning in a teenager.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Tekerek et al (1) found in their study that the most common cause of drug intoxication in adolescence is suicide attempts. After the stabilization of the patient's medical situation, we requested a child and adolescent psychiatry consultation in order to detect possible suicide attempts and other psychopathologies.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Tekerek et al (1) found in their study that the most common cause of drug intoxication in adolescence is suicide attempts. After the stabilization of the patient's medical situation, we requested a child and adolescent psychiatry consultation in order to detect possible suicide attempts and other psychopathologies.…”
Section: Dear Editormentioning
confidence: 99%
“…Dear Editor, Polat et al (1) described nicely the clinical picture, management plan, and favorable outcome of a case of alpha-lipoic acid (ALA) intoxication in a 16-year-old Turkish girl. On the basis of her medical history, Polat et al (1) mentioned that the patient took three pills, each of 600 mg ALA, approximately 2 hours before hospital admission to self-treat her headache with intervals of half an hour. I assume that the claimed self-treatment should not mask the potential suicidal attempt in the studied patient.…”
mentioning
confidence: 99%
“…Alpha lipoic acid (ALA) is an antioxidant, which is used to eliminate the free radicals and metal ions chelation as well as reduce vitamin C and cytosolic glutathione (Polat et al, 2020). ALA is released by the enzymatic activity of lipoic-acid synthase in plant and animal cells.…”
Section: Introductionmentioning
confidence: 99%